2000
DOI: 10.1038/sj.leu.2401830
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD44 variant exons in acute myeloid leukemia is more common and more complex than that observed in normal blood, bone marrow or CD34+ cells

Abstract: CD44 is an adhesion molecule that is expressed on hematopoietic cells and has been implicated in the interactions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 37 publications
(32 reference statements)
1
26
0
Order By: Relevance
“…The CD44 isoform accounting for adhesion to the BM niche was not consistently evaluated. LIC adhesion to the BM niche may rely on an embryonic CD44v isoform (Holm et al, 2015) or may profit from CD44v expression (Bendall et al, 2000; Liu and Jiang, 2006; Redondo-Muñoz et al, 2010) or differ between leukemia subtypes as elaborated for CML-like myeloproliferative neoplasia and AML LIC, which use diverse mechanisms for niche embedding (Krause et al, 2013), the majority of LIC apparently compete with HSC for the BM niche via CD44s binding. CD44/HA also is engaged in CIC homing.…”
Section: Linking Cd44/cd44v6 Activities To Cic Featuresmentioning
confidence: 99%
“…The CD44 isoform accounting for adhesion to the BM niche was not consistently evaluated. LIC adhesion to the BM niche may rely on an embryonic CD44v isoform (Holm et al, 2015) or may profit from CD44v expression (Bendall et al, 2000; Liu and Jiang, 2006; Redondo-Muñoz et al, 2010) or differ between leukemia subtypes as elaborated for CML-like myeloproliferative neoplasia and AML LIC, which use diverse mechanisms for niche embedding (Krause et al, 2013), the majority of LIC apparently compete with HSC for the BM niche via CD44s binding. CD44/HA also is engaged in CIC homing.…”
Section: Linking Cd44/cd44v6 Activities To Cic Featuresmentioning
confidence: 99%
“…The adhesion molecule CD44 has been identified as a therapeutic target in AML due to its altered properties in AML blasts and association with poor prognosis and high relapse rates in AML as well as many solid tumors [14,15,[48][49][50][51][52]. Highly efficient blocking of CD44 was previously achieved using anti-CD44 moAb in AML and resulted in anti-tumor activity in leukemia xenografts [12]; however, the requirement of complex processes with high cost for therapeutic moAbs production and the possibility of adverse effects including immune reactions, infections, autoimmune diseases, cancer, platelet and thrombotic disorders, and cardiotoxicity by administration of moAbs are still major concerns [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CD44 was identified as a crucial surface receptor on BCR-ABL-positive LSPC of chronic myeloid leukemia (CML) involved in homing, migration and retention in the BM [13]. More importantly, clinical experience indicates that CD44 is associated with poor prognosis of AML, and high CD44 levels are associated with higher relapse rates [14,15]. In support of its crucial role in AML relapse, it has been recently reported that the high level expression of CD44 by AML cells was sufficient to generate leukemia by leukemia-initiating cells even after withdrawal of the HoxA10 gene overexpression event that initiated the leukemia [16].…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing of v6-containing variant isoforms in bone marrow MNCs from APL patients Total RNA was extracted with TRIZOL (Invitrogen) and used for reverse transcription into cDNA. In the presence of DNA polymerase (Promega, Madison, WI, USA), PCR was performed using previously described procedures (LJ et al, 2000): pre-denaturation at 95°C for 5 min; 35 cycles of denaturation at 94°C for 50 s, annealing at 55°C for 30 s and extension at 72°C for 60 s followed by a final extension at 72°C for 10 min. The primers in the PCR were as follows: β-actin: 5'AGTGTGACGTGGACATCCGCAAAG3' (forward), 5'ATCCACATCTG CTGGAAGG TGGAC 3' (reverse); CD44S-v6: 5'TCCAGGCAACTCCTAGTA 3' (forward), 5'-AGTCCACTTGGCTTTCTGTC-3' (reverse); CD44v6-S: 5'-GACGAAGACAGTCCCTGGATCA-3' (forward), 5' CAGCTGTCCCTGTTGTCG3ʼ (reverse).…”
Section: Cell Culturementioning
confidence: 99%